OPERA: Omega-3 Fatty Acids Fail to Prevent Postoperative Atrial Fibrillation - Buckley, Rita (MD Conference Express, 2012)
Postoperative atrial fibrillation (AF) flutter occurs in approximately 1 of 3 patients undergoing cardiac surgery [Hogue CW Jr et al. Chest 2005; Mitchell LB et al. Can J Cardiol 2011], generating a need for new therapies to prevent it and its associated morbidity and healthcare costs [Mozaffarian D et al. JAMA 2012]. This article discusses findings from the Omega-3 Fatty Acids for Prevention of Post-Operative Atrial Fibrillation trial [OPERA; NCT00970489].